2017
DOI: 10.1186/s12934-017-0787-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic network model guided engineering ethylmalonyl-CoA pathway to improve ascomycin production in Streptomyces hygroscopicus var. ascomyceticus

Abstract: BackgroundAscomycin is a 23-membered polyketide macrolide with high immunosuppressant and antifungal activity. As the lower production in bio-fermentation, global metabolic analysis is required to further explore its biosynthetic network and determine the key limiting steps for rationally engineering. To achieve this goal, an engineering approach guided by a metabolic network model was implemented to better understand ascomycin biosynthesis and improve its production.ResultsThe metabolic conservation of Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…In the case of fungi, also producing secondary metabolites, 24 Penicillium GEMs were recently reconstructed using MetaCyc database and a Penicillium rubens GEM as references . Analysis of the resulting Penicillium GEMs revealed that metabolic diversity across the species was observed in secondary metabolism, not primary metabolism, which was consistent with the metabolic conservation analysis of 31 Streptomyces species from another study . GEM‐based pan‐genome analysis will allow better understanding of not just how secondary metabolism works across species, but also evolutionary processes of individual species, including habitats and specific growth conditions.…”
Section: Status Of Genome‐scale Metabolic Reconstruction Of Actinomycsupporting
confidence: 75%
“…In the case of fungi, also producing secondary metabolites, 24 Penicillium GEMs were recently reconstructed using MetaCyc database and a Penicillium rubens GEM as references . Analysis of the resulting Penicillium GEMs revealed that metabolic diversity across the species was observed in secondary metabolism, not primary metabolism, which was consistent with the metabolic conservation analysis of 31 Streptomyces species from another study . GEM‐based pan‐genome analysis will allow better understanding of not just how secondary metabolism works across species, but also evolutionary processes of individual species, including habitats and specific growth conditions.…”
Section: Status Of Genome‐scale Metabolic Reconstruction Of Actinomycsupporting
confidence: 75%
“…ascomyceticus H16. Escherichia coli JM109 was used to propagate all plasmids (Wang, Wang et al, ). E. coli ET12567/pUZ8002 was used as a nonmethylating plasmid donor strain for intergeneric conjugation with S. hygroscopicus var.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli ET12567/pUZ8002 was used as a nonmethylating plasmid donor strain for intergeneric conjugation with S. hygroscopicus var. ascomyceticus (Wang, Wang et al, ). The integrative E. coli ‐ Streptomyces shuttle vector pIB139 containing the ermE * promoter ( P ermE* ) was used for gene overexpression in S. hygroscopicus var.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the capacity of models to give structure and chemical meaning to functional annotations in biology, these models are also valuable for their predictive capacity. Today, models can be used to predict a wide range of biological phenotypes, including: (i) respiration, photosynthesis, and fermentation types (Cheung et al 2014;de la Torre et al 2015;Marcellin et al 2016;Edirisinghe et al 2016;Meadows et al 2016;Mendoza et al 2017;Marshall et al 2017;Chen et al 2018;Shameer et al 2018;Lieven et al 2018); (ii) feasible growth conditions and Biolog phenotype array profiles (Plata et al 2015;Bosi et al 2016;diCenzo et al 2016;Hartleb et al 2016); (iii) essential genes and reactions (Ding et al 2016;Khodayari and Maranas 2016;Zhang et al 2018;Xavier et al 2018;Guzmán et al 2018); (iv) potential existing or engineerable by-product biosynthesis pathways (Alper et al 2005;Milne et al 2011;Park et al 2013;Chen and Henson 2016;Harder et al 2016); and (v) the yields and even titre available for those pathways (Zuñiga et al 2016;Wang et al 2017;Li et al 2018;Niu et al 2019).…”
Section: Introductionmentioning
confidence: 99%